Psychometric properties of the sexual machismo scale (EMS-SEXISMO-12) in adults - Gonzales Ortiz, Esther (2024)
Introduction: Machismo is explained as the system of beliefs, attitudes and behaviors based on the polarization of the sexes and the superiority of the male gender. In the sexual sphere, it is the control that is exercised over a woman in relation to the expression of her sexuality under what is considered acceptable. Therefore, it is considered convenient to have instruments to measure this variable. Objective: The objective of this study was to determine the psychometric characteristics of the sexual machismo scale (Ems-sexismo-12) in adults. Method: The methodology used was of an applied nature, with a non-experimental approach and instrumental design, applying the instrument to a sample made up of 530 adults (M=308 and F=222) aged between 18 and 65 years, obtained through non-probabilistic sampling by quotas of the districts of Piura. The content validity, confirmatory factor analysis (WLSMV estimator), internal consistency and reliability of the scale were evaluated. Results: The results showed content validity in the items (Aiken's V > .70).  For its part, after the confirmatory factor analysis, a unidimensional structure was revealed with satisfactory goodness-of-fit indices (CFI = .96; TLI = .95; RMSEA = .08; SRMR = .06). Likewise, reliability is evidenced with acceptable values (ω = .83). Conclusion: The EMS-12 scale proved to be a valid and reliable instrument for adults.